Repellency of two deet formulations and Avon Skin-So-Soft against biting midges (Diptera: Ceratopogonidae) in Honduras - Magnon, G.J; Robert, L.L; Kline, D.L; Roberts, L.W (Journal of the American Mosquito Control Association, 1991)
Two U.S. military issue deet repellent formulations (75% deet liquid and 33% deet lotion) and Avon Skin-So-Soft were tested against ceratopogonid midges under field conditions in Honduras. Test subjects were U.S. military personnel deployed to Honduras for training. Culicoides furens accounted for 96.3% of all midges collected. The liquid and lotion formulations of deet and Avon Skin-So-Soft provided 97.9, 95.9 and 71.4% protection, respectively, compared with the untreated control. Both deet formulations provided significantly better protection (P less than 0.05) than Avon Skin-So-Soft. The latter provided protection by trapping the midges in the oily film and not by repelling the insects as did the deet formulations.